EFFECT OF PRODUCT ATTRIBUTES, BRAND IMAGE AND SALES PROMOTION ON H&M PURCHASE DECISIONS - Putri, Lutvi Meidina; Wardhani, Intan Dwita; Maulana, Wildan Ahmad; Armadiana, Anisa; Aurelya, Azura Tasya; Pratminingsih, S.A. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research was to examine the impact of product attributes, brand image, and sales promotion on H&M product purchasing decisions in Bandung. This study uses a quantitative approach using the explanatory method through distributing questionnaires. The outcomes of this study proved that the product attribute variables, brand image and sales promotion all have an impact on purchase decisions. This studies is also expected to contribute to the company, especially in its marketing strategy in the form of product and promotion strategies so that they are always updated in providing information, especially in social media. The limitation of this study is that the majority of the selected samples are H&M visitors who are in the city of Bandung. It is hoped that further research will expand the sample and add several variables that can influence purchase decisions.